JUNG'S ARCHETYPE ON THE GOLDEN COMPASS'S CHARACTERS BY PHILIP PULLMAN - Santi Nikethan; Diva Wenanda (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2017)
JUNG'S ARCHETYPE ON THE GOLDEN COMPASS'S CHARACTERS BY PHILIP PULLMAN